Management of a Pregnant Patient With Central Poststroke Pain Syndrome Ultimately Having a Cesarean Delivery: A Case Report. Issue 11 (3rd June 2019) - Kalopita, Konstantina; Skandalou, Vasiliki; Valsamidis, Dimitrios
Abstract : Cerebrovascular events, along with the early presentation of central pain, during pregnancy, are uncommon. We report a case of a parturient with intense central poststroke pain after an ischemic cerebrovascular incident at 15 weeks of gestation, attributed to cerebral venous thrombosis. After a multidisciplinary team consultation, she was scheduled for cesarean delivery at 35 weeks of gestation, under combined spinal-epidural anesthesia. Due to severe left-sided neurological deficits and ipsilateral intense neuropathic pain, the neuraxial technique was successfully performed using the paramedian approach.